Wnt7a is required for regeneration of dystrophic skeletal muscle - Gurriaran-Rodriguez, Uxia; Kodippili, Kasun; Datzkiw, David; Javandoost, Ehsan; Xiao, Fan; Rejas, Maria T.; Rudnicki, Michael A. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Intramuscular injection of Wnt7a has been shown to accelerate and augment skeletal muscle regeneration and to ameliorate dystrophic progression in mdx muscle, a model for Duchenne muscular dystrophy (DMD). Here, we assessed muscle regeneration and function in wild type (WT) and mdx mice where Wnt7a was deleted in muscle using a conditional Wnt7a floxed allele and a Myf5-Cre driver. We found that both WT and mdx mice lacking Wnt7a in muscle, exhibited marked deficiencies in muscle regeneration at 21 d following cardiotoxin (CTX) induced injury. Unlike WT, deletion of Wnt7a in mdx resulted in decreased force generation prior to CTX injury. However, both WT and mdx muscle lacking Wnt7a displayed decreased force generation following CTX injection. Notably the regeneration deficit in mdx mice was rescued by a single tail vein injection of extracellular vesicles containing Wnt7a (Wnt7a-EVs). Therefore, we conclude that the regenerative capacity of muscle in mdx mice is highly dependant on the upregulation of endogenous Wnt7a following injury, and that systemic delivery of Wnt7a-EVs represents a therapeutic strategy for treating DMD.